La Relación Entre el Conocimiento y la Práctica en Reanimación Cardiopulmonar Básica Pediátrica de los Estudiantes de Licenciatura en Enfermería - Guadalupe Daniel Cebreros González; Gendi del Rosario Leyva Castro; Cesar David Elizalde González (Ibero Ciencias - Revista Científica y Académica - ISSN 3072-7197, 2026)
Pediatric basic cardiopulmonary resuscitation (CPR) was considered an essential competency in the education of nursing students; however, questions remained regarding the relationship between theoretical knowledge and practical performance of this technique. The objective of this study was to analyze the relationship between these two variables among sixth-semester undergraduate nursing students at the Autonomous University of Baja California, Mexicali Campus, during the 2025-2 academic term. A quantitative, correlational study was conducted with a sample of 76 students. Data were collected using a 15-item Likert-scale questionnaire with a Cronbach's alpha coefficient of 0.70, indicating acceptable reliability. The data were analyzed using descriptive statistics and Pearson's correlation coefficient with SPSS version 27. The results showed a favorable level of knowledge regarding the fundamental principles of pediatric cardiopulmonary resuscitation, particularly in compression-to-ventilation ratio, activation of the emergency medical services (EMS), and the use of the automated external defibrillator (AED). However, inferential analysis revealed a very weak relationship between theoretical knowledge and practical performance, indicating that conceptual mastery alone did not ensure adequate execution of resuscitation maneuvers. It was concluded that, although the students demonstrated satisfactory theoretical knowledge, it was necessary to strengthen the development of practical skills through educational strategies based on clinical simulation and meaningful learning. The main contribution of this study was to provide evidence on the relationship between knowledge and practice in pediatric cardiopulmonary resuscitation among nursing students, thereby supporting the design of educational interventions aimed at enhancing clinical competencies and improving pediatric patient safety.